Sex differences in maturational timing of amygdala and prefrontal cortex volumes and white matter tract microstructure - Jamie Roeske; Xiangyu Long; Meaghan V Perdue; Madison Long; Bryce Geeraert; Mohammad Ghasoub; Keith Owen Yeates; Catherine Lebel (Developmental Cognitive Neuroscience)
The developmental mismatch hypothesis (DMH) proposes that a mismatch in maturational timing of the amygdala and prefrontal cortex (PFC) drives adolescent sensation-seeking behaviour. While some studies provide support for the DMH, few have evaluated sex differences or examined both grey and white matter. Here, we used T1-weighted and diffusion-weighted magnetic resonance imaging (MRI) to examine amygdala and PFC macrostructure and amygdala-PFC white matter microstructure development across 606 MRI sessions from 148 typically developing children and adolescents (76 females) aged 1.95–17.71 years. Using generalized additive mixed effects models, we evaluated the maturational timing of amygdala volume, four PFC subregion volumes, and fractional anisotropy and mean diffusivity of the uncinate fasciculus and amygdala-PFC white matter tracts. Amygdala and PFC maturation was consistent with the DMH in males but less so in females. Relative to males, females exhibited less amygdala development and shorter periods of PFC development. In contrast to gray matter volumes, white matter changed continuously from early childhood to late adolescence, but ended earlier in females than in males. Our findings show different amygdala-PFC maturation patterns and that the amygdala-PFC neural system reaches maturity earlier in females than in males. These important differences may underlie sex differences in sensation-seeking behaviour.